2014
DOI: 10.1097/wno.0000000000000073
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient and Emergency Service Utilization in Patients With Idiopathic Intracranial Hypertension

Abstract: The ED was commonly used by patients with IIH, with a mean of 2.7 visits per patient. The rate of a missed diagnosis was similar to another published series and is concerning for potentially permanent visual loss in undiagnosed patients. In our experience, the ICD-9 code vastly overestimated the number of ED and inpatient encounters attributable to IIH. This has important implications for research studies, particularly those relying on national inpatient databases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 5 publications
2
23
0
Order By: Relevance
“…Koerner et al 15 found a similarly low PPV (55%) when validating patient visits at emergency and inpatient clinics, as did Fisayo 16 (PPV 60%) when reevaluating patients at a neuro-ophthalmological department. Koerner et al 15 found a similarly low PPV (55%) when validating patient visits at emergency and inpatient clinics, as did Fisayo 16 (PPV 60%) when reevaluating patients at a neuro-ophthalmological department.…”
Section: Validation Of Diagnosismentioning
confidence: 91%
See 1 more Smart Citation
“…Koerner et al 15 found a similarly low PPV (55%) when validating patient visits at emergency and inpatient clinics, as did Fisayo 16 (PPV 60%) when reevaluating patients at a neuro-ophthalmological department. Koerner et al 15 found a similarly low PPV (55%) when validating patient visits at emergency and inpatient clinics, as did Fisayo 16 (PPV 60%) when reevaluating patients at a neuro-ophthalmological department.…”
Section: Validation Of Diagnosismentioning
confidence: 91%
“…Finding IIH patients using the Swedish National Patient Register (NPR) alone showed a low positive predictive value (PPV) of 65% (definite cases PPV=54%) using the modified Dandy Criteria. Koerner et al 15 found a similarly low PPV (55%) when validating patient visits at emergency and inpatient clinics, as did Fisayo 16 (PPV 60%) when reevaluating patients at a neuro-ophthalmological department. This indicates that setting a correct diagnosis of IIH can be difficult (particularly early on with frequent change in diagnosis on reevaluation), and coding in registers is also associated with errors (for example, not having a better code to use and typing mistakes when documenting the code).…”
Section: Validation Of Diagnosismentioning
confidence: 91%
“…In most cases, IIH is managed in the outpatient setting. Thus, effective transitions from emergency and inpatient settings, where the initial diagnostic work up often occurs, 94 are critical to optimize outcomes. Challenges in relation to social deprivation exist among some patients 95 which, in turn, is associated with poorer access to health care.…”
Section: Delivery Of Carementioning
confidence: 99%
“…The authors reviewed 145 cases, of whom 27 had contemporaneous CSF opening pressures and compared them to 50 age‐matched control subjects in whom IIH was not suspected. The diagnosis was based on ICD codes, which are not highly reliable for this purpose, and the charts were not reviewed to determine whether or not the patients truly had IIH. About half of cases showed single or multiple sites of venous outflow obstruction in the dominant‐side circulation in suspected IIH cases, most commonly in the transverse sinus but also in the sigmoid sinuses and jugular bulbs.…”
Section: The Venous Sinusesmentioning
confidence: 99%